Commercial Human Spaceﬂights: Legal Challenges for International Regulation - V. Kumar; K. D. Raju; S. R. Subramanian (BRICS Law Journal, 2021)
Commercial Human Spaceﬂight – a new addition to the commercial activities in outer space – is attracting the ultra-rich section of the society. It has enormous potential to accelerate the economic aspect of commercial spaceﬂight since with the development of reusable technologies it is expected to become cheaper. At the same time, it poses a severe threat in various ways to the status quo of the existing regime of space regulation. Taking humans to outer space as a passenger aﬀects the current social, psychological, political, and legal setup. The paper highlights the legal issues that are arising from commercial human spaceflights. Therefore, in section one, the article discusses applicable international law to this emerging activities. Part two details speciﬁcally on the international space law that is relevant to regulate these activities. After analyzing the existing international law on space activities in sections one and two, which are essential for the commercial human spaceﬂights, part three identiﬁes several legal challenges that are not suﬃciently addressed by the existing laws. Section four examines the role played by the regulatory organization to develop the space law, and the role of the International Civil Aviation Organisation (ICAO) has been discussed in detail. As the ICAO holds good experience in handling air transportation, many believe that the ICAO is naturally well placed to regulate commercial space transportation. This aspect has been elaborated in detail in this part. In the ﬁfth, i.e. the last section, the authors conclude by arguing to develop a new international convention to regulate it.